Teaching Academic Words With Digital Flashcards: Investigating the Effectiveness of Mobile-Assisted Vocabulary Learning for University Students - Xodabande, Ismail; Iravi, Yasaman; Mansouri, Behzad; Matinparsa, Hoda (Frontiers in Psychology, 2022)
The current study explored the effects of using digital flashcards (DFs) and mobile devices on learning academic vocabulary. The participants were 86 university students majoring in Psychology in two experimental conditions and one control group. A list of 361 core academic words frequently used in Psychology was taught to the participants using different materials and the learning outcomes were compared across the three groups. Accordingly, the participants in the experimental group 1 (N = 31) used a DF application (i.e., NAWL builder), participants in the experimental group 2 (N = 30) used traditional materials (i.e., paper flashcards), and those in the control group were given a list of target words with their definitions. Receptive knowledge of the target words was tested before and after the treatment, and the learning outcomes were compared across the groups using one way between-groups analysis of variance (ANOVA). The findings of the study indicated that using DFs enhanced students’ engagement with learning their discipline-specific academic vocabulary and that experimental group 1 outperformed those participants in other learning conditions. The findings add to the existing literature on mobile-assisted vocabulary learning and provide empirical support for the effectiveness of such platforms for learning academic vocabulary. The implications of the study were discussed in terms of the affordances provided by DFs on mobile devices and corpus-based word lists for informing vocabulary learning components in teaching English for Academic Purposes (EAP).